Expression and clinical significance of Numb and Notch-1 proteins between tissue of colon cancer and regional lymph node metastases - Ma, Jingyou; Zhen, Jinpeng; Yang, Ningbao; Meng, Changjuan; Lian, Yanjun (Frontiers in Oncology, 2024)
ObjectiveTo investigate the expression and clinical significance of Notch-1 and Numb protein in colon cancer tissues and regional lymph node metastases.MethodsImmunohistochemical method was used to detect the expression of Notch-1 protein and Numb protein in 110 cases of colon cancer tissues, along with tumor adjacent tissues and 56 cases of MLN tissues, and to analyze its role in colon cancer and MLN tissue.ResultsComparing colon cancer tissue or lymph node metastases with tumor adjacent tissue, the positive expression rate of Numb was significantly decreased, while the positive expression of Notch-1 was significantly increased in colon cancer tissue or lymph node metastases (both p<0.05). The expression of Notch-1 and Numb was correlated with the lymph node metastasis, TNM stage, and degree of differentiation (p<0.05). The expression between Numb and Notch-1 showed negative correlation in colon cancer tissues (r=−0.261, p<0.05). There was no relationship between the expression of Numb and Notch-1 protein in colon cancer and metastatic lymph node tissue (p>0.05).ConclusionNumb expression is decreased and Notch-1 expression is increased in colon cancer tissue and metastatic lymph node tissue, suggesting that the interaction between the two proteins may play a promote role in the development, invasion, and metastasis of colon cancer. There was no relationship between the expression of Numb and Notch-1 protein in colon cancer and metastatic lymph node tissue, suggesting that there is no obvious enhancement of the cancer cells; in the process of lymph node metastasis, the degree of malignant biological behavior remains relatively stable.